The Effect of Murabahah Financing and Profit Sharing on the Profitability of Return on Assets (ROA) Through Non Performing Financing (NPF) In Sharia Commercial Banks - Marliyah Marliyah; Kamilah K; Rahmadina Rahmadina (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine how much influence murabahah financing and profit sharing (mudharabah and musyarakah) have on the profitability of Return On Assets (ROA) mediated by Non Performing Financing (NPF). The sample used in this study was 10 BUS in an annual form from 2014 to 2019, and the approach used was a quantitative approach. This study used 60 samples which were processed using the panel data regression analysis method using the eviews 9 application. The results of the analysis showed that this study produced a coefficient of determination (R-square) in the structural model I which was 70.7% of the murabahah, mudharabah, and musyarakah financing variables. affect ROA in Islamic commercial banks while 29.3% is explained by other variables. The results of the coefficient of determination (R-square) model II, which is 72.2% of the murabahah, mudharabah and musyarakah financing variables affect ROA in Islamic commercial banks while 27.8% is influenced by other variables. This study shows that murabahah, mudharabah, musyarakah and NPF financing have a simultaneous effect on ROA with a significance level of 0.001 < 0.05. From the results of the indirect effect significance test, it was found that there was no significant indirect effect of murabahah financing and profit sharing variables (mudharabah and musharaka on ROA profitability ratios through NPF as an intervening variable in Islamic commercial banks.